The role of neutrophils in destruction of vascular endothelium in myocardial revascularization surgeries under extracorporeal circulation - V. V. Novitsky; S. P. Choumakova; O. I. Ourazova; V. M. Shipoulin; T. V. Yemelyanova (Бюллетень сибирской медицины, 2005)
Aimed at studying endothelial destruction dependence on functional activity of neutrophils, 42 patients with ischemic heart disease (IHD) were examined before, 6 and 24 hours after coronary artery bypass grafting (CABG) under extracorporeal circulation. Level of active forms of oxygen (AFO) in blood neutrophiles, their receptor apparatus (CD18-, Fcg- and C3b-receptors), degranulation and desquamation expression of endothelium were estimated. Clinical course of IHD was shown to be accompanied by the stimulation of AFO production by neutrophils as well as cellular digestion ability, by depression of neutrophils receptors expression and marked endothelial destruction. After CABG, the revealed disorders aggravated, degranulation of neutrophils was noted. Interrelation between neutrophils’ AFO production and endothelial alteration was observed only 6 hours after the surgery.